Coal-based hard carbon as well as preparation method and application thereof
Through the ionic liquid extraction and carbonization process, combined with the carbon coating step, the problems of harsh conditions, large waste liquid volume and poor electrical performance in the existing coal-based hard carbon preparation methods are solved, and the effects of simplifying the process, reducing waste liquid and improving electrical performance are achieved.
Patent Information
- Application Number
- CN202411949416.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-04-11
AI Technical Summary
The existing coal-based hard carbon preparation methods have problems such as harsh conditions, large waste liquid volume, and poor electrical performance.
The coal raw materials are extracted and deazened by ionic liquid, and then carbonized to prepare coal-based hard carbon, and carbon coating is carried out after the carbonization step to improve electrical performance.
The process flow is simplified, the waste liquid volume is reduced, and the electrochemical performance of coal-based hard carbon is improved, including the optimization of specific surface area and pore structure.
Abstract
Description
Technical Field
[0001] The present invention relates to the field of battery negative electrode materials, and in particular to coal-based hard carbon and a preparation method and application thereof. Background Art
[0002] The battery mainly includes positive electrode, negative electrode, electrolyte, separator, current collector, etc. Among them, hard carbon is the preferred negative electrode material. At present, the types of precursors of hard carbon as negative electrode materials mainly include biomass, resin, and coal. Compared with biomass and resin, coal-based precursors have the advantage of low cost.
[0003] When coal-based hard carbon is used as the negative electrode material of sodium-ion batteries, it has the advantages of high energy density and good cycle stability. However, the ash content in the precursor of coal-based hard carbon is high, which will reduce the electrochemical properties of hard carbon such as gram capacity, first efficiency, and rate performance, thus affecting the overall performance of the battery.
[0004] At present, the deashing method of coal-based hard carbon precursor is mainly acid-base deashing, which is to wash the coal-based hard carbon precursor with strong acid or strong base to remove the ash therein. For example, it can be washed with strong acid such as hydrofluoric acid, sulfuric acid, nitric acid, etc., or with strong base such as sodium hydroxide and potassium hydroxide. See the steps disclosed in Chinese patent application document CN115207320A, which uses biomass material walnut shell as raw material, and undergoes crushing, water washing, acid washing, water washing, mixing alkali, and drying.
[0005] The above disclosed acid-base deashing method for coal-based hard carbon precursor can effectively deash, but the reaction conditions are relatively harsh and need to be carried out under high temperature and high pressure, which not only increases the production cost, but also places high requirements on equipment. In addition, the existing disclosed acid-base deashing method will produce a large amount of waste liquid, and the treatment of this waste liquid is also a problem. In addition, the acid-base deashing method also has the problem of damaging the structure of the hard carbon, affecting its electrochemical performance.
[0006] Moreover, for coal with medium and low metamorphic degrees, the impurity content is relatively high. When it is used as raw material to prepare coal-based hard carbon, its electrical performance has disadvantages such as low specific capacity and low initial efficiency compared with coal-based hard carbon prepared from other coal raw materials. Summary of the invention
[0007] Therefore, the technical problem to be solved by the present invention is that the currently disclosed method for preparing coal-based hard carbon has the defects of harsh conditions, large amount of waste liquid, and poor electrical properties of the prepared coal-based hard carbon, so as to provide coal-based hard carbon and its preparation method and application that solve the above problems.
[0008] A method for preparing coal-based hard carbon, comprising:
[0009] Coal raw material acquisition;
[0010] Extraction, using ionic liquid to treat the coal raw material and separate the deashed coal-based hard carbon precursor;
[0011] Carbonization: Carbonizing a coal-based hard carbon precursor to obtain coal-based hard carbon.
[0012] The above-mentioned preparation method of the present invention is applicable to all types of coal raw materials, and is particularly applicable to medium and low metamorphic coal with relatively high impurity content, that is, the coal raw material is medium and low metamorphic coal; the metamorphic degree of the coal raw material is usually determined by parameters such as volatile matter (V), vitrinite reflectance (R), carbon content (C), hydrogen content (H), moisture (M), calorific value (Q), etc. The metamorphic degree of the coal raw material in the present invention is mainly defined by the volatile matter and the maximum reflectance of the vitrinite. The medium and low metamorphic coal in the present invention is The volatile content is 20wt%-50wt%, and the maximum reflectivity of the vitrinite group is 0.4%-1.6%. For example, the volatile content of the medium and low metamorphic coal is 20wt%, 25wt%, 30wt%, 35wt%, 40wt%, 45wt%, 50wt%, etc., and the maximum reflectivity of the vitrinite group is 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1.0%, 1.1%, 1.2%, 1.3%, 1.4%, 1.5%, 1.6%, etc. As a preferred setting, the volatile content of the medium and low metamorphic coal is preferably 25%-35%, and the maximum reflectivity of the vitrinite group is 0.7%-1.4%.
[0013] The volatile matter content of medium and low metamorphic coal is relatively high. If the existing direct carbonization method is used, it will lead to the loss of this part of volatile matter, and it is necessary to increase the volatile matter treatment step in the carbonization process, making the carbonization process complicated. The present invention uses ionic liquid extraction to extract and recycle this part of light components, effectively avoiding the additional volatile matter treatment step in the subsequent carbonization process and simplifying the carbonization process.
[0014] In the present invention, ionic liquid extraction has three purposes: 1. Remove ash from coal; 2. Extract and recycle light components in coal, especially aliphatic light components; 3. The precursor has a low specific surface area and an underdeveloped pore structure. Ionic liquid extraction can enrich the pore structure of the precursor, which is beneficial to subsequent carbon coating and improving electrical properties. The ionic liquid used in the present invention can be one or more of an acidic ionic liquid, an alkaline ionic liquid or a neutral ionic liquid, and the ash in the precursor can also be further reduced by a series extraction method. As a preferred setting, in the extraction step of the ionic liquid, the mass ratio of the coal raw material to the ionic liquid is 1: (0.5-20), for example, the mass ratio is 1: 0.5, 1: 0.6, 1: 0.7, 1: 0.8, 1: 0.9, 1: 1, 1: 2, 1: 4, 1: 6, 1: 8, 1: 10, 1: 12, 1: 14, 1: 16, 1: 18, 1: 20, etc., preferably 1: (1-3). The processing temperature of the extraction step is 20-80°C, for example, the processing temperature is 20°C, 25°C, 30°C, 35°C, 40°C, 45°C, 50°C, 55°C, 60°C, 65°C, 70°C, 75°C, 80°C, etc., preferably 30-50°C; the processing time is 0.5-24h, for example, the processing time is 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 5h, 6h, 8h, 10h, 15h, 20h, 24h, etc., preferably 2-6h. The ash content in the coal raw material (the ash content detected by the industrial analysis method of coal in GB / T212-2008) is ≤20wt%, for example, the ash content is 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, 11wt%, 12wt%, 13wt%, 14wt%, 15wt%, 16wt%, 17wt%, 18wt%, 19wt%, 20wt%, etc. Through the extraction treatment of the above-mentioned ionic liquid, the ash content in the coal-based hard carbon precursor is ≤10wt%, and the ash content can usually be reduced to 0.05wt%-10wt%, for example, the ash content is 1wt%, 2wt%, 3wt%, 4wt%, 5wt%, 6wt%, 7wt%, 8wt%, 9wt%, 10wt%, etc.
[0015] In order to minimize the residue of ionic liquid on the surface of coal raw materials, the coal raw materials after ionic liquid extraction need to be separated by filtering and washing to remove the ionic liquid on the surface of the coal raw materials. After removing the ionic liquid, a coal-based hard carbon precursor is obtained.
[0016] At the same time, the ionic liquid after separation can be recycled by removing the light components. For example, washing and reduced pressure distillation can be used to remove the light components in the ionic liquid, and the ionic liquid with the light components removed can be recycled and reused, greatly reducing the amount of waste liquid.
[0017] The present invention further comprises the steps of drying and crushing the coal raw material before the extraction, wherein the drying temperature is 100-125°C, for example, the drying temperature is 100°C, 105°C, 110°C, 115°C, 120°C, 125°C, etc., and the preferred drying temperature is 100-120°C. After drying is completed, subsequent crushing treatment is carried out. The crushing methods include any one or more of the crushing methods such as ball milling, air flow milling, roller milling, and stirring milling. No matter which crushing method is adopted, as long as the particle size of the crushed coal raw material can be 0.01-74μm, as a preferred setting, the D50 particle size of the crushed coal raw material is 0.01-15μm, for example, the D50 particle size is 0.01μm, 0.05μm, 0.1μm, 0.5μm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm, etc.
[0018] In the carbonization step of the present invention, carbonization is performed under a high temperature inert atmosphere; in the carbonization step, the high temperature is 1000-1600°C, for example, the high temperature is 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, 1600°C, etc., preferably 1000-1400°C, and the carbonization time is 1-4h, for example, the carbonization time is 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, etc., preferably 1-2h. The inert atmosphere is N 2 , Ar or He atmosphere.
[0019] Coal-based hard carbon after direct ionic liquid deashing and carbonization has the problems of large specific surface area and more open pore structure. Direct use will reduce the capacity and initial efficiency. In order to further improve the capacity and initial efficiency, the carbonization step in the present invention also includes a carbon coating process; as a preferred coating method, the carbon coating process is: solid-phase mixing of a carbon source and the carbonized coal-based hard carbon and sintering to obtain the final carbon-coated coal-based hard carbon.
[0020] In the above-mentioned carbon coating, the carbon source of the carbon coating is one or more of asphalt and thermoplastic resin; the carbon coating method adopts solid-phase mechanical mixing or solid-phase ball milling mixing, and the mixing time is 0.02h-24h, for example, the mixing time is 0.02h, 0.05h, 0.1h, 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 5h, 6h, 8h, 10h, 15h, 20h, 24h, etc., preferably 2-6h; in the process of sintering after mixing, the treatment is carried out under an inert atmosphere, and the type of carrier gas of the inert atmosphere is N 2Or Ar; wherein the sintering temperature is 400-1500°C, for example, the sintering temperature is 400°C, 500°C, 600°C, 700°C, 800°C, 900°C, 1000°C, 1100°C, 1200°C, 1300°C, 1400°C, 1500°C, etc., preferably 900-1300°C; the sintering time is 0.5-6h, preferably 1-3h.
[0021] The present invention also provides a coal-based hard carbon, which is prepared by the above-mentioned preparation method.
[0022] The invention provides an application of coal-based hard carbon as a negative electrode active material in a negative electrode or a battery.
[0023] The present invention also provides a negative electrode material, comprising the above-mentioned coal-based hard carbon.
[0024] The present invention also provides a battery, comprising the above-mentioned negative electrode material. The battery in the present invention is preferably a sodium ion battery.
[0025] The technical solution of the present invention has the following advantages:
[0026] 1. The present invention provides a method for preparing coal-based hard carbon, which can be prepared by extracting and deashing coal raw materials with ionic liquid and then carbonizing them; the method of the present invention has the advantages of simplifying the process, reducing the amount of waste liquid, and improving the electrical properties of coal-based hard carbon; the realization mechanism of the above advantages is as follows:
[0027] The present invention only uses one step of ionic liquid extraction to achieve the purpose of removing ash, which greatly simplifies the process steps compared to the conventional acid-base ash removal method; the separated ionic liquid can be recycled and reused, greatly reducing the amount of waste liquid generated during the preparation process; and the ionic liquid extraction will also remove the light components of the coal raw material at the same time, effectively replacing the method in which the light components need to be incinerated during carbonization in the traditional process, simplifying the carbonization process steps. At the same time, the present invention uses the ionic liquid extraction method to extract the light components in the coal raw material, remove part of the ash and enrich the pore structure of the coal raw material, which is beneficial to the improvement of the electrical properties of the coal-based hard carbon prepared later; specifically, the coal raw material has a low specific surface area and an underdeveloped pore structure. The light components in the coal raw material, especially the aliphatic light components, can be extracted by ionic liquid extraction, and the ash in the coal raw material can be removed at the same time, thereby enriching the pore structure of the coal raw material, achieving the purpose of improving the electrical properties of the coal-based hard carbon.
[0028] 2. The present invention provides a method for preparing coal-based hard carbon, wherein a carbon coating step is further added. In the carbon coating step, a solid phase mixing method is used for carbon coating, which can further simplify the carbon coating process and improve the electrical properties of the coal-based hard carbon. DETAILED DESCRIPTION
[0029] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.
[0030] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.
[0031] Example 1
[0032] A method for preparing coal-based hard carbon, comprising:
[0033] S1. Obtaining coal raw materials;
[0034] The coal raw material used in this embodiment is low-medium metamorphic coal, the maximum reflectivity of the vitrinite of the low-medium metamorphic coal is 0.9%, the volatile matter content is 32wt%, and the ash content is 9.05%.
[0035] S2, drying and crushing;
[0036] 1000 g of coal raw material was dried in an oven at 110° C. for 12 h, and then ground and crushed by a double-roll mill to obtain coal powder with a particle size of D50: 13.5 μm, D90: 20 μm, and D100: 35 μm.
[0037] S3, extraction;
[0038] Take 20g of coal powder at a time and place it in a container. Add the acidic ionic liquid 1-butyl-3-methylimidazolium tetrachloride ferric salt ([bmim]FeCl 4 ) 20g, and add 40g of anhydrous ethanol as a dispersant. The container is placed in an ultrasonic disperser for dispersion, extraction and deashing. The temperature of the ultrasonic disperser is 50°C. The ultrasonic and extraction deashing is performed for 6 hours. First, the solid coal is washed and filtered with anhydrous ethanol, and then the solid coal is filtered, washed and dried with deionized water until the pH value of the filtrate is between 6-8. Finally, a deashed coal-based hard carbon precursor is obtained; the ash content in the coal-based hard carbon precursor is reduced from 9.05% in the original coal powder to 2.5%;
[0039] The liquid extraction product was mixed with deionized water and placed in an ultrasonic disperser for dispersion and ultrasonication. The temperature of the disperser was 50°C and the ultrasound was carried out for 2 hours. The solid components ash and aliphatic components in the liquid extraction product were separated by vacuum filtration again. The ionic liquid in the filtrate was recovered by vacuum distillation for reuse.
[0040] S4, carbonization;
[0041] The coal-based hard carbon precursor was heated in a tubular resistance furnace under an inert atmosphere of N 2 High temperature carbonization is carried out at a temperature of 1200°C and a carbonization time of 2h. After the carbonization is completed, carbonized coal-based hard carbon is prepared.
[0042] S5, carbon coating;
[0043] The carbonized coal-based hard carbon precursor was subjected to carbon coating. Specifically, asphalt powder was used as the coating carbon source, the softening point of the asphalt powder was 175°C, and the particle size D50 of the asphalt powder was 5.2 μm. 10 g of the carbonized coal-based hard carbon was mixed with 5 g of asphalt powder and ball-milled for 2 h; after ball milling, sintering was performed, and the type of carrier gas used in the sintering process was N 2 The sintering temperature is 900℃ and the sintering time is 2h; after sintering, coal-based hard carbon which can be used as a negative electrode material for batteries is finally obtained.
[0044] The coal-based hard carbon prepared as above is used as the negative electrode material of the battery to prepare the negative electrode, metallic sodium is used as the positive electrode, a sodium hexafluorophosphate solution with a concentration of 1M is used as the electrolyte, and the solvent of the electrolyte is a carbonate organic solvent; the negative electrode, the positive electrode, and the electrolyte are assembled into a button cell by a conventional method, and the assembled button cell is tested for the charge and discharge capacity and the first efficiency of the hard carbon negative electrode at a current density of 20mA / g. The button cell prepared in this embodiment has a reversible capacity of 255mAh / g and a first efficiency of 85.1%.
[0045] Example 2
[0046] A method for preparing coal-based hard carbon, comprising:
[0047] S1. Obtaining coal raw materials;
[0048] The coal raw material used in this embodiment is low-medium metamorphic coal, the maximum reflectivity of the vitrinite of the low-medium metamorphic coal is 0.9%, the volatile matter content is 32wt%, and the ash content is 9.05%.
[0049] S2, drying and crushing;
[0050] 1000 g of coal raw material was dried in an oven at 110° C. for 12 h, and then ground and crushed by a double-roll mill to obtain coal powder with a particle size of D50: 13.5 μm, D90: 20 μm, and D100: 35 μm.
[0051] S3, extraction;
[0052] Take 20g of coal powder at a time and place it in a container, add 300g of acidic ionic liquid 1-methyl-3-ethylimidazolium hydrofluoride EMIm(HF)nF (see EMIm(HF)nF published in "Journal of Physical Chemistry B" Volume 109 / Issue 12 on March 9, 2005) at a time, and add 300g of N-methylpyrrolidone (NMP) as a dispersant. Place the container in an ultrasonic disperser for dispersion, extraction and deashing. The temperature of the ultrasonic disperser is 30°C. Ultrasonic and extraction deashing is performed for 20 hours. First, the solid coal is washed and filtered with anhydrous ethanol, and then the solid coal is filtered, washed and dried with deionized water until the pH value of the filtrate is between 6 and 8. Finally, a deashed coal-based hard carbon precursor is obtained; the ash content in the coal-based hard carbon precursor is reduced from 9.05% in the original coal powder to 1.82%;
[0053] The liquid extraction product was mixed with deionized water and placed in an ultrasonic disperser for dispersion and ultrasonication. The temperature of the disperser was 50°C and the ultrasound was carried out for 2 hours. The solid components ash and aliphatic components in the liquid extraction product were separated by vacuum filtration again. The ionic liquid in the filtrate was recovered by vacuum distillation for reuse.
[0054] S4, carbonization;
[0055] The coal-based hard carbon precursor was heated in a box-type resistance furnace under an inert atmosphere of N 2 High temperature carbonization is carried out at a temperature of 1400°C and a carbonization time of 4 hours. After the carbonization is completed, a carbonized coal-based hard carbon precursor is prepared.
[0056] S5, carbon coating;
[0057] The carbonized coal-based hard carbon precursor was subjected to carbon coating. Specifically, phenolic resin (PE powder) was used as the coating carbon source, and the particle size D50 of the phenolic resin was 3.5 μm. 10 g of the carbonized coal-based hard carbon was mixed with 3 g of phenolic resin and ball-milled for 24 h; after ball milling, sintering was performed, and the type of carrier gas used in the sintering process was N 2 The sintering temperature is 1200℃ and the sintering time is 0.5h; after sintering, coal-based hard carbon that can be used as a negative electrode material for batteries is finally obtained.
[0058] The coal-based hard carbon prepared as above is used as the negative electrode material of the battery to prepare the negative electrode, metallic sodium is used as the positive electrode, a sodium hexafluorophosphate solution with a concentration of 1M is used as the electrolyte, and the solvent of the electrolyte is a carbonate organic solvent; the negative electrode, the positive electrode, and the electrolyte are assembled into a button cell by a conventional method, and the assembled button cell is tested for the charge and discharge capacity and the first efficiency of the hard carbon negative electrode at a current density of 20mA / g. The button cell prepared in this embodiment has a reversible capacity of 263mAh / g and a first efficiency of 84.3%.
[0059] Example 3
[0060] A method for preparing coal-based hard carbon, comprising:
[0061] S1. Obtaining coal raw materials;
[0062] The coal raw material used in this embodiment is low-medium metamorphic coal, the maximum reflectivity of the vitrinite of the low-medium metamorphic coal is 0.9%, the volatile matter content is 32wt%, and the ash content is 9.05%.
[0063] S2, drying and crushing;
[0064] 1000 g of coal raw material was dried in an oven at 110° C. for 12 h, and then ground and crushed by a double-roll mill to obtain coal powder with a particle size of D50: 13.5 μm, D90: 20 μm, and D100: 35 μm.
[0065] S3, extraction;
[0066] Take 20g of coal powder at a time and place it in a container. Add neutral ionic liquid 1-butyl-3-methylimidazolium tetrafluoroborate ([Bmim]BF 4 ) 100g, and add 100g of anhydrous ethanol as a dispersant. The container is placed in an ultrasonic disperser for dispersion, extraction and deashing. The temperature of the ultrasonic disperser is 70°C. The ultrasonic and extraction deashing is performed for 1 hour. First, the solid coal is washed and filtered with anhydrous ethanol, and then the solid coal is filtered, washed and dried with deionized water until the pH value of the filtrate is between 6 and 8. Finally, a deashed coal-based hard carbon precursor is obtained; the ash content in the coal-based hard carbon precursor is reduced from 9.05% in the original coal powder to 3.9%;
[0067] The liquid extraction product was mixed with deionized water and placed in an ultrasonic disperser for dispersion and ultrasonication. The temperature of the disperser was 50°C and the ultrasound was carried out for 2 hours. The solid components ash and aliphatic components in the liquid extraction product were separated by vacuum filtration again. The ionic liquid in the filtrate was recovered by vacuum distillation for reuse.
[0068] S4, carbonization;
[0069] The coal-based hard carbon precursor was heated in a rotary kiln under an inert atmosphere of N 2 High temperature carbonization is carried out at 1600°C and the carbonization time is 6h. After the carbonization is completed, a carbonized coal-based hard carbon precursor is prepared.
[0070] S5, carbon coating;
[0071] The carbonized coal-based hard carbon precursor was subjected to carbon coating. Specifically, phenolic resin was used as the coating carbon source, and the particle size D50 of the phenolic resin was 12 μm. 10 g of the carbonized coal-based hard carbon was mixed with 10 g of phenolic resin (PE powder) and ball-milled for 10 h; after ball milling, sintering was performed, and the type of carrier gas used in the sintering process was N 2 The sintering temperature is 1500℃ and the sintering time is 4h; after sintering, coal-based hard carbon that can be used as a negative electrode material for batteries is finally obtained.
[0072] The coal-based hard carbon prepared as above is used as the negative electrode material of the battery to prepare the negative electrode, metallic sodium is used as the positive electrode, a sodium hexafluorophosphate solution with a concentration of 1M is used as the electrolyte, and the solvent of the electrolyte is a carbonate organic solvent; the negative electrode, the positive electrode, and the electrolyte are assembled into a button cell by a conventional method, and the assembled button cell is tested for the charge and discharge capacity and the first efficiency of the hard carbon negative electrode at a current density of 20mA / g. The button cell prepared in this embodiment has a reversible capacity of 251mAh / g and a first efficiency of 82.7%.
[0073] Example 4
[0074] The difference between this embodiment and embodiment 1 is that the raw coal is different, and the ionic liquid used in the S3 extraction step of this embodiment is a neutral ionic liquid 1-butyl-3-methylimidazolium hexafluorophosphate ([Bmim]BF 6 ), and other conditions are the same as those in Example 1; in this step, the ash content in the coal-based hard carbon precursor is reduced from 9.05% in the original coal powder to 4.2%.
[0075] The button cell prepared in this example has a reversible capacity of 243 mAh / g and a first efficiency of 82.5%.
[0076] Example 5
[0077] The difference between this embodiment and embodiment 1 is that the raw coal is different. The ionic liquid used in the S3 extraction step of this embodiment is the alkaline ionic liquid 1-butyl-3-methylimidazolium hydroxide ([Bmim]OH), and the other conditions are the same as those in embodiment 1. The ash content in the coal-based hard carbon precursor is reduced from 9.05% in the original coal powder to 3.8%.
[0078] The button cell prepared in this example has a reversible capacity of 262 mAh / g and a first efficiency of 84.5%.
[0079] Example 6
[0080] The difference between this embodiment and embodiment 1 is that the raw coal is different. The ionic liquid used in the S3 extraction step of this embodiment is the neutral ionic liquid 1-butyl-3-methylimidazolium chloride ([Bmim]Cl), and the other conditions are the same as those in embodiment 1. The ash content in the coal-based hard carbon precursor is reduced from 9.05% in the original coal powder to 4.8%.
[0081] The button cell prepared in this example has a reversible capacity of 232 mAh / g and a first efficiency of 82.1%.
[0082] Example 7
[0083] The difference between this embodiment and embodiment 1 is that the raw coal is different. The coal raw material in this embodiment is medium-low metamorphic coal, the maximum reflectivity of the vitrinite group of the medium-low metamorphic coal is 1.4%, the volatile matter content is 30wt%, and the ash content is 10.2wt%; at the same time, the coal powder particle size D50 after step S2 is 3.5μm, and other conditions are the same as those in embodiment 1.
[0084] After the S3 extraction step, the ash content in the coal-based hard carbon precursor is reduced from 10.2wt% in the original coal powder to 2.80%; the button battery prepared in this embodiment has a reversible capacity of 223mAh / g and a first efficiency of 82%.
[0085] Example 8
[0086] The difference between this embodiment and embodiment 1 is that the raw coal is different. The coal raw material in this embodiment is medium-low metamorphic coal, the maximum reflectivity of the vitrinite group of the medium-low metamorphic coal is 0.5%, the volatile matter content is 34.78wt%, and the ash content is 15.03%; at the same time, the coal powder particle size D50 after step S2 is 0.5μm, and other conditions are the same as those in embodiment 1.
[0087] After the S3 extraction step, the ash content in the coal-based hard carbon precursor is reduced from 15.03% in the original coal powder to 5.5%; the button battery prepared in this embodiment has a reversible capacity of 198 mAh / g and a first efficiency of 75.4%.
[0088] Example 9
[0089] The difference between this embodiment and embodiment 8 is that there is no carbon coating step of S5, and the carbonized coal-based hard carbon is directly used as the negative electrode material of the battery. The rest is exactly the same as embodiment 1.
[0090] The button cell prepared in this example has a reversible capacity of 184 mAh / g and a first efficiency of 74.1%.
[0091] Example 10
[0092] The present embodiment is different from the embodiment 1 in that the raw coal is different. The raw coal in the present embodiment is medium-low metamorphic coal, the maximum reflectivity of the vitrinite group of the medium-low metamorphic coal is 0.8%, the volatile matter content is 32.5wt%, and the ash content is 9.1%; at the same time, the particle size D50 of the coal powder after step S2 is 6.8μm, and the alkaline ionic liquid 1-butyl-3-methylimidazolium acetate ([BMIM]Ac) is added in step S3, and the other conditions are the same as those in embodiment 1.
[0093] After the S3 extraction step, the ash content in the coal-based hard carbon precursor is reduced from 9.1% in the original coal powder to 1.9%; the button battery prepared in this embodiment has a reversible capacity of 242 mAh / g and a first efficiency of 85.6%.
[0094] Comparative Example 1
[0095] The difference between this comparative example and Example 9 is that there is no extraction step of S3, and the coal powder in S2 is directly used for carbonization in step S4. The rest is exactly the same as Example 1.
[0096] The button cell prepared in this comparative example has a reversible capacity of 168 mAh / g and an initial efficiency of 72.1%.
[0097] By comparing the results of this comparative example 1 with the results of Example 9, it can be seen that Example 9 uses ionic liquid to extract and deash the coal raw material, and then carbonizes it. Compared with the present comparative example without deashing, the reversible capacity of the prepared button battery can be increased by 16 mAh / g, and the first efficiency is increased by 2%.
[0098] Comparative Example 2
[0099] The difference between this comparative example and Example 9 is that the extraction step of S3 is replaced by an acid-base elution deashing method, and the rest is exactly the same as Example 1. The specific process of S3 is as follows:
[0100] Take 20g of coal powder at a time and place it in a container, stir and soak it in 60℃ pure water for 4h, wash with water and filter three times; add 1mol / L hydrochloric acid and 1mol / L hydrofluoric acid in sequence, remove the filtrate by suction when changing the acid, heat to 80℃ for acid washing for 2h, the solid-liquid mass ratio is 1:10, filter and wash several times until the filtrate is close to neutral; add 1% NaOH of the coal powder mass and appropriate amount of water to the filter cake, stir into slurry and mix evenly, dry at 105℃, and finally obtain a deashed coal-based hard carbon precursor; the ash content in the coal-based hard carbon precursor is reduced from 15.3% in the original coal powder to 3.2%.
[0101] The button cell prepared in this comparative example has a reversible capacity of 176 mAh / g and a first efficiency of 73.2%.
[0102] By comparing the results of this comparative example with those of Example 9, it can be seen that the method of Example 9 using ionic liquid to extract and deash the coal raw material and then carbonizing it can increase the reversible capacity of the prepared button battery by 7.3 mAh / g and the first efficiency by 0.9% compared with the acid-base washing and deashing method used in this comparative example.
[0103] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A method for preparing coal-based hard carbon, characterized in that: include: Coal raw material acquisition; Extraction, using ionic liquid to treat the coal raw material and separate the deashed coal-based hard carbon precursor; Carbonization: Carbonizing a coal-based hard carbon precursor to obtain coal-based hard carbon.
2. The preparation method according to claim 1, characterized in that: The coal raw material is medium-low metamorphic coal, the volatile matter content of the medium-low metamorphic coal is 20wt%-50wt%, and the maximum reflectivity of the vitrinite group is 0.4%-1.6%.
3. The preparation method according to claim 1 or 2, characterized in that: In the extraction step, the mass ratio of the coal raw material to the ionic liquid is 1:(0.5-20), preferably 1:(1-3).
4. The preparation method according to any one of claims 1 to 3, characterized in that The treatment temperature of the extraction step is 20-80°C, preferably 30-50°C; the treatment time is 0.5-24h, preferably 2-6h; And / or, the ash content of the coal-based hard carbon precursor is ≤20wt%, preferably ≤10wt%.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the carbonization step, the carbonization temperature is 1000-1600° C., preferably 1000-1400° C., and the carbonization time is 1-4 hours, preferably 1-2 hours; And / or, the coal raw material is dried and crushed before extraction; And / or, after the carbonization step, a carbon coating process is also included; And / or, in the extraction step, the separated ionic liquid is recycled after light components are removed.
6. The preparation method according to claim 5, characterized in that: The drying temperature is 100°C-125°C; And / or, the particle size of the crushed coal raw material is 0.01 μm-74 μm; And / or, the carbon coating process is: solid phase mixing of a carbon source and carbonized coal-based hard carbon and sintering to obtain carbon-coated coal-based hard carbon; And / or, the method for removing the light components includes washing and reduced pressure distillation.
7. The preparation method according to claim 6, characterized in that: The D50 particle size of the crushed coal raw material is 0.01-15 μm, preferably 3-10 μm; And / or, the sintering temperature is 400-1500° C., preferably 900-1300° C.; the sintering time is 0.5-6 h, preferably 1-3 h; And / or, the solid phase mixing method is solid phase mechanical mixing or solid phase ball milling mixing, and the mixing time is 0.02h-24h, preferably 2-6h.
8. A coal-based hard carbon, characterized in that: The preparation method is described in any one of claims 1 to 7.
9. Use of the coal-based hard carbon according to claim 8 as a negative electrode active material in a negative electrode or a battery.
10. A negative electrode material or a battery, characterized in that: Comprising the coal-based hard carbon as described in claim 8.
Citation Information
Patent Citations
Preparation method of lithium / sodium ion battery negative electrode material
CN115207320A
Cited By
Method for extracting fullerene from acetylene black conductive agent waste coke
CN122187017A